Benefits of quiet workspaces in open-plan offices – Evidence from two office relocations. (April 2018) - Haapakangas, Annu; Hongisto, Valtteri; Varjo, Johanna; Lahtinen, Marjaana
Abstract: The problems of open-plan offices are widely known. However, the factors explaining these effects have received less attention. The aim of this study was to investigate the role of office distractions in the emergence of other problems, and to examine the benefits of quiet workspaces in open-plan offices. Two organizations moved from private offices to open-plan offices that differed in the number and variety of quiet rooms. Survey data was gathered once before (N = 65 and 64) and once after the office relocation (N = 135 and 71). Perceived distractions increased in both organizations after the relocation. However, negative effects on environmental satisfaction, perceived collaboration and stress only emerged in the open-plan office where the number of quiet rooms was low. Increased distractions mediated the effects on collaboration and stress. Quiet workspaces, and the perceived ease of access to them, are associated with environmental perceptions, perceived collaboration and employee stress in open-plan offices. Highlights: Distractions are a central source of environmental stress in open-plan offices. Increased distractions mediate other negative effects of an office relocation. An increase in distractions may impair collaboration and increase stress symptoms. Providing quiet workspaces improves work conditions in open-plan offices.